Six plays of Clifford Odets, Clifford Odets - Odets, Clifford, frey50 (New York, The Modern library, 1939)
In the spring of 1935, when Waiting for Lefty was first produced by the Group Theatre, a new force made itself felt in the American drama. Since then Clifford Odets has extended and solidified his reputation as the most brilliant playwright of the younger generation. Each of his plays reveals an impressive developement of his dramatic gifts. This volume includes all his work to date in their complete texts.
Waiting for Lefty.--Awake and sing!--Till the day I die.--Paradise lost.--Golden boy.--Rocket to the moon.--Appendix: three introductions by Harold Clurman: 1. Awake and sing! 2. Paradise lost. 3. Golden boy.
Includes preface by the author
Keywords: American Drama -- Plays -- 20th Century